Determinan Pengungkapan Emisi Karbon Perusahaan Energi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Ganiardy, Faustine; Viriany, Viriany (Fakultas Ekonomi Universitas Gresik, 2023)
Disclosure of carbon emissions is prepared by companies with the aim of knowing the performance and impact of company activities on greenhouse gas emissions. This research was conducted with the aim to prove the effect of profitability, firm size, and leverage on the disclosure of carbon emissions empirically. The population used in this study is energy sector companies listed on the Indonesia Stock Exchange from 2020 to 2022. Through a purposive sampling technique, 13 companies with a total of 39 observational data were selected for the study and will be further analyzed using multiple linear regression analysis techniques. The research results prove that profitability and leverage do not have a significant effect on disclosure of carbon emissions. Company size has a significant positive effect on disclosure of carbon emissions